2020
DOI: 10.1186/s40900-020-00187-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from participatory research to enhance client participation in long-term care research: a multiple case study

Abstract: Background Although participatory research is known to have advantages, it is unclear how participatory research can best be performed. This study aims to report on lessons learned in collaboration with service users involved as co-researchers in three participatory teams in long-term care. Methods A multiple case study design was chosen to explore the collaboration in three teams, each covering one specific client group receiving long-term care: physically or mentally frail elderly people, people with mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…While representing a broad variety of expertise (supporting people who are communication-vulnerable, designing and implementing complex interventions, and behaviour change) they were responsible for design and content decisions based on the care-users, professionals and management input. Lofman (2004) and Scheffelaar (2020) emphasised the possible unequal relationships between the researchers and care-users and the importance of relationship-building to overcome this issue [ 34 , 35 ]. Our study showed that, especially for the care-users, cherishing relationships and creating a safe environment enabled this group to feel supported to participate.…”
Section: Discussionmentioning
confidence: 99%
“…While representing a broad variety of expertise (supporting people who are communication-vulnerable, designing and implementing complex interventions, and behaviour change) they were responsible for design and content decisions based on the care-users, professionals and management input. Lofman (2004) and Scheffelaar (2020) emphasised the possible unequal relationships between the researchers and care-users and the importance of relationship-building to overcome this issue [ 34 , 35 ]. Our study showed that, especially for the care-users, cherishing relationships and creating a safe environment enabled this group to feel supported to participate.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the privacy of study participants, the coresearchers sign a confidentiality agreement. Two important conditions for participatory research were yielded by a previous multiple case study 36 : a good working environment and good collaboration. These conditions can be achieved by the organisation of training sessions, availability of the researcher, (financial) appreciation and a clear division of roles.…”
Section: Methods and Analysismentioning
confidence: 99%
“…For the analysis of the results, co-researchers were expected to share their experiences, give advice and participate in the discussions of the work meetings. Results were summarised by the team and communicated to the respondents to provide them with general information on the study findings 39…”
Section: Methodsmentioning
confidence: 99%